Characterization of cochlear implant artifacts in electrically evoked auditory steady-state responses. (January 2017) - Deprez, Hanne; Gransier, Robin; Hofmann, Michael; van Wieringen, Astrid; Wouters, Jan; Moonen, Marc
Abstract : Highlights: Stimulation artifacts obscure auditory steady state responses in cochlear implants (CIs). The artifacts can be characterized based on their amplitude growth and duration. These properties are dependent on reference electrode position. The artifacts can be removed at contralateral electrodes for stimulation up to 500 Hz. Abstract: Objective: Electrically evoked auditory steady-state responses (EASSRs) are neural potentials measured in the electroencephalogram (EEG) in response to periodic pulse trains presented, for example, through a cochlear implant (CI). EASSRs could potentially be used for objective CI fitting. However, EEG signals are contaminated with electrical CI artifacts. In this paper, we characterized the CI artifacts for monopolar mode stimulation and evaluated at which pulse rate, linear interpolation over the signal part contaminated with CI artifact is successful. Methods: CI artifacts were characterized by means of their amplitude growth functions and duration. Results: CI artifact durations were between 0.7 and 1.7 ms, at contralateral recording electrodes. At ipsilateral recording electrodes, CI artifact durations are range from 0.7 to larger than 2 ms. Conclusion: At contralateral recording electrodes, the artifact was shorter than the interpulse interval across subjects for 500 pps, which was not always the case for 900 pps. Significance: CI artifact-free EASSRs are crucial for reliable CI fitting and neuroscience research. The CI artifact has been characterized and linear interpolation allows to remove it at contralateral recording electrodes for stimulation at 500 pps.